Histopathological Pattern of Spinal Tumor: Experience of 57 Cases in Bangladesh (Bangladesh Journal of Neurosurgery, 2020)
Background: Spinal cord tumors are presented with different histopathological pattern.Objective: The purpose of the present study was to see the different histopathological pattern of spinal tumor.Methodology: This descriptive cross sectional study was conducted in the Department of Neurosurgery at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2016 to December 2019 for a period of 04 (Four) years. Patients presented with spinal tumor were selected as study population. After surgical removal the spinal tumor, tissue was sent for histopathological examination to the Department of Neuropathology of the same institute.Result: A total number of 57 spinal tumor cases were recruited for this study. The male and female ratio was 1.34:1. Out of 57 spinal tumor mostly were located in the intradural extramedullary (IDEM) which was 39(68.4%) cases. Extradural and intramedullary were found in 7(12.3%) cases in each. Most of the spinal tumor were Schwannoma which was 28(49.1%) cases. Neurofibroma and meningioma were found in 6(10.5%) cases in each. Lipoma was found in 3(5.3%) cases. Ependymoma was found in 4(7.0%) cases.Conclusion: In conclusion Schwannoma is the most common variant of spinal tumor detected among the study population.Bang. J Neurosurgery 2020; 10(1): 27-32